Iron ore mineral´s evaluation, exploration and prospecton by geophysical methods - Castro-Gaitán, Sandra Marcela; Rodríguez-Vega, Gehovell Yadira (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2007)
The outcomes in an iron mineral prospection and exploration, made in the municipality of Firavitoba (Boyacá-Colombia) are exposed, with the aim to define the material continuity. Three geophysical methods were selected: The Magneto-metric, the Vertical Electrical Sounding and the body loaded. Once these studies were processed in the software SURFER & and IPI"WIN,  was obtained: The magnetic anomaly map; the area's geophysical geologic profile and an isohomas map. Their interpretation define the mineral continuity, the mineralization roof's approximate depth, and which is the most appropriate sector for exploitation with the eyessight toward a great scale mining's scale mining's beginning.